Dibutyltin Dichloride Retards Leydig Cell Developmental Regeneration in Adult Rat Testis - Xiande Huang (Frontiers in Pharmacology, 2018)
Dibutyltin dichloride (DBTCl), widely used as plastic stabilizer, can cause comprehensive toxicity. The present study aims to investigate the effects of DBTCl on rat Leydig cell developmental regeneration and characterize the related mechanism. Adult male Sprague Dawley rats were randomly divided into four groups and gavaged with saline (control) or 5, 10, or 20 mg/kg/day of DBTCl consecutively for 10 days. At the end of the DBTCl treatment, all rats received a single intraperitoneal injection (i.p.,) of 75 mg/kg ethane dimethane sulfonate (EDS) to eliminate all the adult Leydig cells and to induce Leydig cell developmental regeneration. Leydig cell developmental regeneration was evaluated by measuring the levels of serum testosterone, luteinizing hormone, and follicle-stimulating hormone on days 7, 35, and 56 post-EDS. Leydig cell gene and protein expression levels, as well as cell morphology and cell counts were also carried out on day 56 post-EDS. The present study found that DBTCl significantly reduced serum testosterone levels on days 35 and 56 post-EDS, but increased serum luteinizing hormone (LH) and follicle-stimulating hormone (FSH) levels on day 56 at ≥ 5 mg/kg/day. The mRNA and protein levels of Leydig (Lhcgr, Scarb1, Star, Cyp11a1, Hsd17b3, and Hsd11b1) and Sertoli cells (Fshr, Amh, and Sox9) were significantly downregulated in the DBTCl-treated testes compared to the control. Immunohistochemical staining showed that DBTCl-treatment caused fewer regenerated Leydig cells and impaired Sertoli cell development and function in the testis on day 56 post-EDS. In conclusion, the present study demonstrates that DBTCl retards rat Leydig cell developmental regeneration by downregulating steroidogenesis-related enzymes at the gene and protein levels, inhibiting Leydig cell proliferation and impairing Sertoli cell function and development.